If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(X + 2)(2x + -10) = 0 Reorder the terms: 3(2 + X)(2x + -10) = 0 Reorder the terms: 3(2 + X)(-10 + 2x) = 0 Multiply (2 + X) * (-10 + 2x) 3(2(-10 + 2x) + X(-10 + 2x)) = 0 3((-10 * 2 + 2x * 2) + X(-10 + 2x)) = 0 3((-20 + 4x) + X(-10 + 2x)) = 0 3(-20 + 4x + (-10 * X + 2x * X)) = 0 3(-20 + 4x + (-10X + 2xX)) = 0 Reorder the terms: 3(-20 + -10X + 4x + 2xX) = 0 3(-20 + -10X + 4x + 2xX) = 0 (-20 * 3 + -10X * 3 + 4x * 3 + 2xX * 3) = 0 (-60 + -30X + 12x + 6xX) = 0 Solving -60 + -30X + 12x + 6xX = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '60' to each side of the equation. -60 + -30X + 12x + 60 + 6xX = 0 + 60 Reorder the terms: -60 + 60 + -30X + 12x + 6xX = 0 + 60 Combine like terms: -60 + 60 = 0 0 + -30X + 12x + 6xX = 0 + 60 -30X + 12x + 6xX = 0 + 60 Combine like terms: 0 + 60 = 60 -30X + 12x + 6xX = 60 Add '-12x' to each side of the equation. -30X + 12x + -12x + 6xX = 60 + -12x Combine like terms: 12x + -12x = 0 -30X + 0 + 6xX = 60 + -12x -30X + 6xX = 60 + -12x Reorder the terms: -60 + -30X + 12x + 6xX = 60 + -12x + -60 + 12x Reorder the terms: -60 + -30X + 12x + 6xX = 60 + -60 + -12x + 12x Combine like terms: 60 + -60 = 0 -60 + -30X + 12x + 6xX = 0 + -12x + 12x -60 + -30X + 12x + 6xX = -12x + 12x Combine like terms: -12x + 12x = 0 -60 + -30X + 12x + 6xX = 0 Factor out the Greatest Common Factor (GCF), '6'. 6(-10 + -5X + 2x + xX) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(-10 + -5X + 2x + xX)' equal to zero and attempt to solve: Simplifying -10 + -5X + 2x + xX = 0 Solving -10 + -5X + 2x + xX = 0 Move all terms containing X to the left, all other terms to the right. Add '10' to each side of the equation. -10 + -5X + 2x + 10 + xX = 0 + 10 Reorder the terms: -10 + 10 + -5X + 2x + xX = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -5X + 2x + xX = 0 + 10 -5X + 2x + xX = 0 + 10 Combine like terms: 0 + 10 = 10 -5X + 2x + xX = 10 Add '-2x' to each side of the equation. -5X + 2x + -2x + xX = 10 + -2x Combine like terms: 2x + -2x = 0 -5X + 0 + xX = 10 + -2x -5X + xX = 10 + -2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 8x^2=26x+357 | | .81t^2+140=0 | | 4+(-3)2= | | (x+5)=(3x-1) | | -0.3-2.7=-4.1 | | B+8=2 | | 5(r+3)=4+2r+2 | | x-2.3=6.4 | | 750=y+(y*.07) | | 15-3x=7x+5 | | 6cos-1=2 | | 4(q)=52 | | 2(4x+1)=3x-9x | | 1996.43x=7385-67x | | R-(-5)=9 | | 8(4-n)+2=90 | | 44221=a*2+b | | 2(5x+7)+3=10x+17 | | 2x-17=2x-12 | | 3(r+7)=15 | | 4r-1=-4+4r+3 | | -4(x+9)=7-3x | | 2(4x-10)=46 | | 3m+3=5 | | -15+3=-2(x+7) | | 1996+43x=3716 | | 3x+3=(x+3) | | 10(a-2)=-70 | | -86=-7n+4(-n-5) | | 7-3x-5-3x=5 | | Kx-3x=-2+5k | | 360-76= |